Probing the Sodium Insertion/Extraction Mechanism in a Layered NaVO3 Anode Material - Ali, Ghulam; Islam, Mobinul; Jung, Hun-Gi; Nam, Kyung-Wan; Chung, Kyung Yoon (American Chemical Society, 2018)
For the realization of sodium-ion batteries (SIBs), high-performance anode materials are urgently required with the advantages of being low-cost and environment-friendly. In this work, layered-type NaVO3 is prepared by the simple solid-state route with a rod-like morphology and used as an anode material for SIBs. The NaVO3 electrode exhibits a high specific capacity of 196 mA h g(-1) during the first cycle and retains a capacity of 125 mA h g(-1) at the 80th cycle with a high Coulombic efficiency of >99%, demonstrating high reversibility. The sodium diffusion coefficient in NaVO3 is measured using electrochemical impedance spectroscopy (1.368 x 10(-15) cm(2) s(-1)), the galvanostatic intermittent titration technique (1.15715 x 10(-13) cm(2) s(-1)), and cyclic voltammetry (2.7935 x 10(-16 )cm(2) s(-1)). Furthermore, the reaction mechanism during the sodiation/desodiation process is investigated using in situ X-ray diffraction and X-ray absorption near the edge structure analysis, which suggests the formation of an amorphous-like phase and reversible redox reaction of V4+ <--> V5+, respectively.
Keywords: LITHIUM-ION BATTERIES; CATHODE MATERIAL; HIGH-CAPACITY; INTERCALATION; PERFORMANCE; STORAGE; OXIDE; NANOCOMPOSITE; ELECTROLYTE; COMPOSITE